Chronic disease comorbidity patterns among elderly Chinese based on CHALS data and their impact on daily living ability - Jianing Zhang; Haoyu Liu; Mengqi Li; Zeyuan Wang; Yutong Chen (Journal of Public Health and Preventive Medicine, 2026)
Objective: To analyze the current prevalence and clustering patterns of chronic comorbidities among elderly people in China, explore the association between different comorbidity patterns and impairment of basic daily living ability (BADL) and instrumental ability of daily living (IADL), and test the moderating effects of physical exercise and social support, providing empirical evidence for formulating precise elderly health management strategies. Methods: Using cross-sectional data from the 2018 China Health and Elderly Care Tracking Survey (CHARLS), 11,246 elderly people aged 60 and above were selected as study subjects. Latent category analysis (LCA) was used to identify chronic disease comorbidity patterns, and logistic regression models were used to analyze the number of comorbidities and their association with BADEL and IADL impairment, to test interaction effects, and to conduct multiple robustness tests. Results: The chronic disease comorbidity rate among the elderly in China was 59.9%, with severe comorbidities (≥ 5 types) accounting for 10.5%. LCA identified five comorbidity patterns: cardiometabolic (26.8%), musculoskeletal-digestive (20.5%, with Chinese population specificity), respiratory-psychiatric (15.3%), multisystem impairment (14.0%), and relative health (23.4%, with 4.2% still having BADAL impairment and 14.3% having IADL impairment in this group). The number of comorbidities was significantly graded and cumulatively associated with impaired daily living ability. The risk of BADAL and IADL impairment in severely comorbid elderly patients was 9.12 times higher (OR=9.12, 95% CI: 7.28-11.43) and 7.89 times higher (OR=7.89, 95% CI: 6.65-9.36), respectively. There was significant heterogeneity in the impact of different comorbidity modes on function, with multisystem impairment at the highest risk, and respiratory-psychiatric types causing significantly more IADL damage than cardiometabolic types. Interaction analysis showed that physical exercise and social support had a significant buffering effect on the association between comorbidity and IADL impairment (interaction term p